1997
DOI: 10.1097/00001888-199706000-00020
|View full text |Cite
|
Sign up to set email alerts
|

A systematic analysis of how medical school characteristics relate to graduatesʼ choices of primary care specialties

Abstract: The results suggest that the most effective way to increase the number of physicians with generalist practices is to increase the number of students interested in a family medicine career at matriculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 0 publications
1
50
0
3
Order By: Relevance
“…Research funding has not been found to relate to choice of family practice 23,27 Based on this somewhat limited body of research, it seems that research funding is not directly related to production of primary care graduates and, as suggested by Bland et al, 9 most probably influences the characteristics and values of the faculty attracted to the school who in turn influence the attitudes of the students who are taught by them.…”
Section: School Research Fundingmentioning
confidence: 99%
See 2 more Smart Citations
“…Research funding has not been found to relate to choice of family practice 23,27 Based on this somewhat limited body of research, it seems that research funding is not directly related to production of primary care graduates and, as suggested by Bland et al, 9 most probably influences the characteristics and values of the faculty attracted to the school who in turn influence the attitudes of the students who are taught by them.…”
Section: School Research Fundingmentioning
confidence: 99%
“…Two studies have found that more primary care faculty on admissions committees 27 and an admission preference for generalists were not related to increased numbers of family medicine graduates. 23 Although these findings are counterintuitive, these data suggest that admissions policies or committees that favor generalism do not have an impact on the production of family physicians.…”
Section: Admission Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Age is a variable that varies considerably among medical students in various countries, along with the percentage of married students; these factors are closely correlated (Senf et al, 1997;Hauer et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Cabe realçar os efeitos potenciais da escola médica -na confirmação ou eliminação da preferência inicial e inclusão de preferência nova -, conforme descrito em vários estudos [6][7][8][9] . As influências abrangem múltiplos aspectos da ambiência institucional, incluindo cenários de formação, currículo e recursos humanos.…”
Section: Introductionunclassified